Coronavirus and sports leagues: how to obtain a fair ranking if the season cannot resume? - Csato, L. (Corvinus University, 2020)
Many sports leagues are played in a tightly scheduled round-robin format, leaving a limited time window to postpone matches. If the season cannot resume due to an external shock such as the coronavirus outbreak in 2020, the ranking of the teamsbecomes non-trivial because it is necessary to account for schedule imbalances. We identify a set of desired axioms for ranking in such incomplete tournaments and verify that the generalized row sum, a parametric family of scoring rules, satisfies all of them. In particular, the well-established least squares method maximizes therole of the opponents. Our approach is applied for the five major premier European soccer competitions, where the rankings are found to be robust concerning the weight of adjustment for the opponents. Since disregarding the majority of the matcheswithout promotion, relegation, and qualification for international cups would be unfair and unjustified, some simpler alternative policies are also discussed